THEORY OF WORK ADJUSTMENT RELATED TO SELF REGULATION AND PSYCOLOGICAL WEEL-BEING ON BK CAREER IN HIGHER EDUCATION - Faris Abdurrahman; Daharnis; Mega Iswari (Literasi Nusantara, 2022)
Work not only acts as a source of fulfillment of various basic life needs, but is also part of the identity of an adult individual as well as a vehicle for achievement and self-actualization.TWA defines this as "satisfaction." Consequently, a suitable job choice is understood as one in which the person is satisfactory in performance and is satisfied with his preferences. Self-adjustment is a continuous individual interaction with oneself, with others, and with the environment in which the individual is located. Self-regulation is the ability to regulate some of the behavior so that it can achieve the expected goals. In achieving individual goals, a good level of regulation must also be supported by a good level of psychological well being. Psychological well being is a condition in which individuals have a positive attitude towards themselves and others, can make their own decisions and can regulate their own behavior, can create and manage an environment that is compatible with their needs, have a purpose in life and make their lives are more meaningful, and trying to explore and develop themselves. Thus the relationship between the Theory of Work Adjustment (TWA) views with self-regulation and psychological well being in higher education is if students are able to regulate or control themselves well, are able to know themselves, have high self-regulation supported by good psychological well being, which is characterized by students are able to create an environment that is compatible with their needs, are able to have a purpose in life and make their lives more meaningful, can achieve a level of job satisfaction, and students will be able to adapt to their work environment.